Acceptance of Internet Banking : Comparing Six Theoretical Models - Rekha, I. S.; Basri, Savitha; Kavitha, T. C. (Indian Journal of Finance, 2020)
The aim of the study was to identify the superior technology adoption model measured in terms of the model's explanatory power in predicting the intention to adopt Internet banking by customers. It examined the behavioral intention to adopt Internet banking by comparing six models namely, technology acceptance model (TAM) (1989), TAM (1996), theory of planned behavior, combined TAM and TPB model, theory of reasoned action, and unified theory of acceptance and use of technology. The survey data were collected from 134 respondents using traditional banking services. The results confirmed combined TAM and TPB model as the superior model compared to the other five models. Since a large proportion of Indians lack digital literacy, it is imperative for banks embarking on digital models to design user friendly websites and online portals, demonstrate the benefits of Internet banking, and thereby, influence the intention to adopt e-banking.